RIFM FRAGRANCE INGREDIENT SAFETY ASSESSMENT, 1-Oxaspiro[4.5]decan-2-one, 8-(1-methylethyl)-, trans-, CAS Registry Number 4625-90-5. (September 2018) - Api, A.M.; Belsito, D.; Botelho, D.; Bruze, M.; Burton, G.A.; Buschmann, J.; Dagli, M.L.; Date, M.; Dekant, W.; Deodhar, C.; Francis, M.; Fryer, A.D.; et al.
Highlights: 1-Oxaspiro[4.5]decan-2-one, 8-(1-methylethyl)-, trans -, safety assessment based on RIFM's criteria. Safety assessment based on 7 human health endpoints plus environmental. All endpoints were cleared using target data, read-across, and/or TTC.